Increasing the Loyalty of Tourists in Batulayang Bogor Tourism Village, West Java, Indonesia, with Operational Risk Management Mediated by Memorable Tourism Experience - Bahri, Asep Syaiful; Sugiarto, Sugiarto; Hendratono, Tonny; Rahmawati, Ema; Are, Robert La (Asian Journal of Social and Humanities, 2025)
The impact of operational risk management on visitors' memorable experiences, intention to return, and intention to refer Batulayang Tourism Village is investigated in this study.  The study tackles the important topic of how poorly managed operational risks, like subpar amenities and safety issues, impact visitor loyalty and pleasure.  Effective risk management is crucial for preserving satisfying experiences and encouraging return visits in Indonesia's tourism industry, which is becoming more and more competitive.  Research on operational risk management in rural tourism communities like Batulayang is still scarce, leaving a gap in our knowledge of its precise effects on rural destinations. Prior studies have concentrated on more general tourism contexts. This study is innovative because it uses a mixed-method approach to provide deeper insights into how risk management might enhance visitors' experiences and affect their future behavior. It focuses on operational risk management in rural tourism settings.  In order to provide useful advice for tourist managers, the study aims to investigate how operational risk management affects visitors' intentions to return and promote the town.  In order to support the sustainable growth of rural tourism in Indonesia, it is anticipated that the findings will assist tourism stakeholders in raising service quality, improving visitor happiness, and boosting industry competitiveness.